SEROPREVALENCE OF HEPATITIS-C CARRIERS AMONG CHILDREN BETWEEN 6 MONTHS TO 15 YEARS OF AGE IN DERA GHAZI KHAN - Muhammad Saleem Channer; Adeen Akram; Muhammad Arslan Saleem et al. (Journal of University Medical & Dental College, 2017)
ABSTRACT: OBJECTIVE: To find out the seroprevalence of viral hepatitis -C carriers among children in Dera Ghazi Khan. DESIGN: An observational descriptive cross-sectional study. SETTING: Dera Ghazi Khan urban slums and Paediatric Medicine Unit in Teaching Hospital Dera Ghazi Khan. SUBJECTS: Two hundred seventy-five children admitted to Paediatric Medicine Unit in Teaching Hospital Dera Ghazi Khan and those in urban slums of Dera Ghazi Khan City. MAIN OUTCOME MEASURES: Seroprevalence of viral hepatitis-C carriers. RESULTS: Mean age of children in our study was 7.5 years. Males were 54%. The number of children detected as carriers of Hepatitis-C was 08 (2.9%). Out of 08 carriers, 04 had successfully completed their EPI schedule, 02 received incomplete vaccination while 02 carriers did not receive any EPI schedule vaccination. Just one seropositive case gave past history of jaundice in his early neonatal period for which he got exchange transfusion. Three of the carriers shared piercing of nose or ears by a common (contaminated) needle. There were no signs suggestive of chronic liver disease in any carrier. CONCLUSION: Overall seroprevalence of viral hepatitis-C carriers in Dera Ghazi Khan is 2.90%. There is a large cohort of seronegative children. They need to be protected against Hepatitis-C virus infection through awareness campaigns.